Comparison of Career Expectation between Nursing Freshman and Interns - Ni Putu Wulan Purnama Sari (Journal of Educational, Health and Community Psychology, 2019)
AbstrakThe growing shortage of nurses is a global issue nowadays. The expectation of student nurses towards their future career as a practical nurse should be carefully considered, especially in the millennial generation. This study aimed to compare and analyze the differences in career expectations between nursing first-year students and interns. This cross-sectional study involved 110 and 66 nursing freshmen and interns, respectively (n=176) in two private nursing colleges in the middle part of Indonesia, both institutions were â€œBâ€ accredited. Career expectations questionnaire was used in data collection. Descriptive statistics and the Mann-Whitney U test were used for analyzing the data (Î±<.05). Results showed that nursing interns had higher career expectations than the freshmen (Mean: 77.24 vs. 71.84); interns had high expectations, while first-year students had enough expectations. There was a significant difference found between groups (p=.003), which influenced by promotion (p=.001), leisure time (p=.015), work-life balance (p=.030), business opportunity (p=.028), organization membership (p=.004), and public recognition (p=.038). Career expectation differs significantly between nursing first-year students and interns.Â Keywords: career, career expectation, nursing, student nurse